Contribution of polymorphisms in the endothelial protein C receptor gene to soluble endothelial protein C receptor and circulating activated protein C levels, and thrombotic risk - Medina, Pilar; Navarro, Silvia; Estellés, Amparo; Vayá, Amparo; Woodhams, Barry; Mira, Yolanda; Villa, Piedad; Migaud-Fressart, Martine; Ferrando, Fernando; Aznar, Justo; Bertina, Rogier M.; España, Francisco (Thrombosis and Haemostasis, 2004)
Endothelial cell protein C receptor (EPCR) enhances the generation of activated protein C (APC) by the thrombin-thrombomodulin complex. A soluble form of EPCR (sEPCR), which is generated by metalloprotease activity, is present in plasma. The distribution of sEPCR levels in healthy populations is bimodal. Previously, we described two polymorphisms in exon 4 of the EPCR gene, 4600A/G that encodes the substitution of Ser219 by Gly in the transmembrane region of EPCR and 4678G/C in the 3’-UT region. The aim of this study was to investigate the relationship between these two polymorphisms and plasma sEPCR and APC levels and risk of venous thrombosis. We genotyped 401 healthy controls from the Spanish population and measured their plasma sEPCR and APC levels. Carriers of the 4600AG genotype had significantly higher sEPCR levels than those with the AA genotype, while the 4678CC genotype was associated, to a lesser extent, with elevated APC levels. To assess the effect of these polymorphisms on the risk of thrombosis, we genotyped 405 patients with venous thromboembolism. The frequency of the 4600AG genotype was very similar in patients and controls (p=0.975), whereas the 4678CC genotype was significantly more frequent in controls than in patients (p=0.008). In multivariate analysis, carriers of the 4678CC genotype had a decreased risk of thrombosis (OR=0.61, p=0.009). These data indicate that individuals carrying the 4600AG genotype have high sEPCR levels but do not have an increased risk of thrombosis, whereas individuals carrying the 4678CC genotype have higher APC levels and lower risk of venous thromboembolism.
Keywords: Protein C; endothelial protein C receptor; polymorphism